Banking crises and investments in innovation - Oana Peia (University College Dublin, UCD School of Economics, 2017)
This paper proposes a new channel to explain the medium- to long-term effects of banking crises on the real economy. It embeds a banking sector prone to runs in a stylized growth model to show that episodes of bank distress affect not only the volume, but also the com- position of firm investment, by disproportionally decreasing investments in innovation. This hypothesis is confirmed empirically employing industry-level data on R&D spending around 13 recent banking crises episodes. Using difference-in-difference identification strategies, I show that industries that depend more on external finance, in more bank-based economies, invest disproportionally less in R&D following systemic banking crises. These industries also have a lower share of R&D spending in total investment, suggesting a shift in the composition of investment that is specific to recessions following banking crises and not other business cycle recessions.
Keywords: G01; G21; E22; 330; banking crises; R&D investment; financial dependence; global games